The Effect of Different Light Curing Units and Tip Distances on Translucency Parameters of Bulk fill Materials - Dana Al-Senan; Hend Al-Nahedh (Elsevier, 2022)
Objectives: To evaluate the effect of light curing unit (LCU) types and distance from light curing unit tip on the translucency parameters (TP) of bulk fill composite materials. Materials and Methods: Two bulk-fill resin composites and one nanohybrid composite were used in this study. The specimens were divided into groups based on the type of curing unit used, and further subdivided based on the distance of the curing source to the surface of the resin composite. Translucency was evaluated at 4 mm thickness (for the bulk-fill) and 2 mm thickness (for nanohybrid) after curing using two different light curing units at zero, 2 mm, and 4 mm distance. The results were analyzed using two-way ANOVA at the significance level of a p-value of < 0.05. Results: Among all the tested materials, Filtek Bulk Fill Posterior RBC showed the highest TP at 0 mm distance when cured with Blue phase G2 LED LCU and it was the least affected by the differences in distances. However, Filtek Z350 nanohybrid composite had no significant differences between the three distances when cured with Blue phase G2 LCU. Conclusion: Translucency values among the studied bulk-fill materials are affected by material composition, curing units and the distance of the tip of the light source to the restoration surface.